2008
DOI: 10.1111/j.1468-1293.2008.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of HIV infection and late initiation of antiretroviral therapy in the Swiss HIV Cohort Study

Abstract: Objectives To investigate delayed HIV diagnosis and late initiation of antiretroviral therapy (ART) in the Swiss HIV Cohort Study. Methods Two sub‐populations were included: 1915 patients with HIV diagnosis from 1998 to 2007 and within 3 months of cohort registration (group A), and 1730 treatment‐naïve patients with CD4≥200 cells/μL before their second cohort visit (group B). In group A, predictors for low initial CD4 cell counts were examined with a median regression. In group B, we studied predictors for CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
72
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 29 publications
14
72
0
5
Order By: Relevance
“…For example, a large Swiss cohort study revealed that about 30% of patients diagnosed with CD4 T cell count below 200 cells/µl and even 10% with below 50 cells/µl [18]. The factors associated with late diagnosis in the Swiss study were increased age and non-Caucasian race, in line with observations from northern France and Brussels, Belgium [19].…”
Section: Discussionsupporting
confidence: 66%
“…For example, a large Swiss cohort study revealed that about 30% of patients diagnosed with CD4 T cell count below 200 cells/µl and even 10% with below 50 cells/µl [18]. The factors associated with late diagnosis in the Swiss study were increased age and non-Caucasian race, in line with observations from northern France and Brussels, Belgium [19].…”
Section: Discussionsupporting
confidence: 66%
“…HTS transmission is described in different countries as an important risk factor in diagnostic delay 16,17,27,28 . It has even been observed that while in some population sub-groups the delay tends to decrease, going from 38% to 25% in 9 years, in others a constant increase can be seen 16,34 . In Barcelona, a study carried out from 2001-2009 showed a decrease in DD only in the first years of the study which then remained stable in the following years 28 .…”
Section: Individual Effects Of Delay In Diagnosismentioning
confidence: 99%
“…National 27,28 and international 34,35,36 studies have associated immigration with an increase in DD. Amongst the causes explaining the delay in these groups are cultural, linguistic and socio-economic barriers, low perception of the risk of acquiring the infection and fear of stigmatisation.…”
Section: Individual Effects Of Delay In Diagnosismentioning
confidence: 99%
“…For Europe as a whole, the percentage of people living with HIV who are diagnosed late in the course of infection ranges from 15% to 38% (Adler, Mounier-Jack, Coker, 2009 (Delpierre et al, 2007). In France, the USA and the United Kingdom, people with heterosexually acquired HIV infection are most likely to be diagnosed late in the course of infection (Delpierre et al, 2007;Centers for Disease Control and Prevention, 2009;Health Protection Agency, 2008), while in Switzerland being non-Caucasian was associated with late diagnosis (Wolbers et al, 2008).…”
Section: Benefits Of Antiretroviral Therapymentioning
confidence: 99%